Virtual rehabilitation in an activity centre for community-dwelling persons with stroke. The possibilities of 3-dimensional computer games - Broeren, Jurgen; Claesson, Lisbeth; Goude, Daniel; Rydmark, Martin; Sunnerhagen, Katharina S (Cerebrovascular diseases (Basel, Switzerland), 2008)
The main purpose of this study was to place a virtual reality (VR) system, designed to assess and to promote motor performance in the affected upper extremity in subjects after stroke, in a nonhospital environment. We also wanted to investigate if playing computer games resulted in improved motor function in persons with prior stroke. The intervention involved 11 patients after stroke who received extra rehabilitation by training on a computer 3 times a week during a 4-week period. The control group involved 11 patients after stroke who continued their previous rehabilitation (no extra computer training) during this period. The mean age of all was 68 years (range = 47-85) and the average time after stroke 66 months (range = 15-140). The VR training consisted of challenging games, which provided a range of difficulty levels that allow practice to be fun and motivating. An additional group of 11 right-handed aged matched individuals without history of neurological or psychiatric illnesses served as reference subjects. All the participants reported that they were novel computer game players. After an initial introduction they learned to use the VR system quickly. The treatment group demonstrated improvements in motor outcome for the trained upper extremity, but this was not detected in real-life activities. The results of this research suggest the usefulness of computer games in training motor performance. VR can be used beneficially not only by younger participants but also by older persons to enhance their motor performance after stroke.